Territoriality Characteristics in Housing of Kampung Bugis, Buleleng Regency, Bali - Ocean Dewata, Kadek; Ketut Agusintadewi, Ni; Anggraini Prajnawrdhi, Tri (ASTONJADRO, 2023)
One of the less well-organized residential areas in Buleleng is the Kampung Bugis settlement. The development of the Bugis Village settlement as one of the densest settlements in Buleleng does not get good regulation and control so that the village environment tends to be slum, disorganized, uncomfortable and unhealthy. The existence of Bugis Village which is increasingly dense by residents also has an impact on the density of buildings in residential areas. Unfortunately, this condition is not balanced with the arrangement and sufficient land area. Due to the high environmental pressure, residents become spatially motivated by creating "new spaces” to meet their individual needs. This is very interesting to examine so that in the future it can be used as a reference for the development of residential areas in the future. Territoriality characteristics that occur in Bugis Village are as follows, land ownership status does not really affect the formation of territorial boundaries, boundary elements are not always a marker of social identity, space that has the highest privacy always has firm territorial boundaries, space resulting from territorial expansion tends to use semi-fixed elements as a territorial marker. This happens because there is still awareness from the residents of the settlements that the expanded land is legally not their property. The territoriality formed in settlements is generally to fulfill six main needs/activities, namely: drying, gathering/playing, trading, storing goods, parking and socializing. Apart from being a territorial marker, some of the boundary elements are an embodiment of aesthetic needs.